USING MODERN INSTRUMENTAL METHODS FOR COFFEE IDENTIFICATION - E. I. Kuzmina; M. Y. Ganin; D. A. Sviridov; O. S. Egorova; A. A. Shilkin; D. R. Akbulatova (Пищевые системы, 2022)
The article provides an analysis of published works devoted to authentication of the place of origin of coffee beans, as well as the research of the main components that can be identification parameters when authenticating coffee. Based on the analysis of scientific literature, the authors noted the most significant works aimed at confirming the authenticity of the place of origin for coffee beans from Ethiopia, Kenya, Hawaii, Costa Rica, Jamaica, Brazil, Guatemala, Mexico and other countries. It was shown that the most widespread studies were aimed at analyzing the values of isotopic ratios of carbon (13C/12C), hydrogen (2H/1H), oxygen (18O/16O) and nitrogen (15N/14N) in compounds contained in coffee beans, which reflect the distribution of “light” and “heavy” isotopes during biological and geochemical processes within the boundaries of a particular region. The authors analyzed the works aimed at studying the qualitative and quantitative composition of trace elements and rare earth metals (Na, Mg, Al, Mn, Ga, Rb, Ba, Pb, Y, La, Ce, Pr, Sm, Nd, Eu, Dy, Gd and others), as well as the research of the values of isotopic ratios (87Sr/86Sr) in product samples and soils of the studied region. Based on the presented materials, it is concluded that the use of the isotope mass spectrometry method in combination with statistical processing of the results makes it possible to determine with a high degree of reliability the product belonging to a certain geographical region, as well as to authenticate the botanical origin of the beans. The advantages of comprehensive research of several indicators using various methods of mathematical statistics and modeling in determining the geographical place of coffee origin are shown.